Tata Kelola Industri Kreatif di Indonesia dalam Perspektif Sound Governance - Nurian Endah Dwi S; Indah Adi Putri; Ria Ariany; Roni Ekha Putera (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The creative industry is the main pillar in developing the creative economic sector which has a positive impact on Indonesia. It is possible that the government has hopes for the Indonesian economy to rise, compete and achieve excellence in the global economy. For this reason, in order to achieve this goal, intervention from various actors is needed, as stated in the Sound Governance perspective, namely the state, civil society, business and international powers. These four important actors will later be analyzed for their interventions in the development of creative industries in Indonesia. This aims to find out how these 4 important actors have an impact on the development of the creative industry in Indonesia. This research was conducted using qualitative research methods. Meanwhile, the type of research used is library research or literature study, where researchers rely on various literature to obtain research data. The conclusion obtained is that of the 4 important actors from the Sound Governance perspective, each has a role and sustainable impact on the development and progress of the creative industry in Indonesia. For this reason, the Government in the concept of Sound Governance must be able to identify the 4 stakeholders who will later be able to develop relationships between the parties involved to obtain the intended results. So that later there will be effective coordination and there will be no disagreements in any political relations written from the SG perspective.